Simulation of The Application of Intelligence in Vernam Cipher Cryptography (One Time Pad) - Agustina Simangunsong; Simanjorang, R. Mahdalena (Sean Institute, 2023)
Technological advances in the field of computers allow thousands of people and computers around the world to be connected in one virtual world known as cyberspace or the Internet. But these technological advances are always accompanied by the downside of the technology itself. One of them is the vulnerability of data security, giving rise to challenges and demands for the availability of a data security system that is as sophisticated as the advancement of computer technology itself. In this study, an algorithm that can secure data will be used which the authors discuss is the Vernam Cipher Algorithm. Vernam Cipher Algorithm is one of the key algorithms. Until now, the Vernam Cipher algorithm is still trusted as an encryption method, Vernam Cipher cryptography uses the same key for encryption and decryption.